The Influence of Learning Environment on Self-Regulated Learning and Learning Outcomes of Students at Ma'had Aly Salafiyah Syafi'iyah Sukorejo - Nurul Azizah; Nurul Umniyatul Bazighoh (Jurnal Pendidikan Islam Indonesia, 2025)
This study aims to analyze the influence of the learning environment on self-regulated learning (SRL) and academic achievement of students at Ma’had Aly Salafiyah Syafi’iyah Sukorejo academic year. Using a quantitative approach with a causal associative design, the study involved 163 students. Instruments used include the Indonesian version of the DREEM Short Form to measure the learning environment, the SRL-SRS (Toering et al., 2012) to assess self-regulated learning, and academic grades as indicators of learning outcomes. Data analysis was performed using the Generalized Additive Models (GAM) due to the non-normal distribution of the dataset. The results of the study showed that the learning environment significantly influenced SRL (F = 55.27; p < 2e-16; adjusted R² = 0.251) with a positive relationship. However, the learning environment did not significantly influence learning outcomes (F = 1.95; p = 0.123; adjusted R² = 0.0354). Other findings showed that SRL significantly influenced learning outcomes (F = 10.15; p < 2e-16; adjusted R² = 0.314). These findings indicate that the learning environment plays an important role in improving SRL among students, and high SRL is associated with better learning outcomes. The study's conclusions confirm that the learning environment plays a dominant role in shaping student independence in learning, which in turn supports their academic achievement. In the context of Islamic boarding schools, strengthening a holistic learning environment is a strategic step in developing independent, critical, and integrated learners